Polatuzumab vedotin plus rituximab with chemotherapy in newly diagnosed pediatric stage IV Burkitt lymphoma: case report highlighting early complete remission - Sun, Yanyan; Deng, Mei; Zhang, Chunlei; Chen, Yanli; Zhang, Yanli; Zuo, Wenli (Frontiers in Immunology, 2025)
Although pediatric Burkitt lymphoma is considered curable, some patients still have a poor prognosis. Lack of early or complete response is an adverse prognostic factor. Therefore, improving patients’ sensitivity to initial treatment and achieving complete remission early are crucial for enhancing efficacy. Herein, we report two cases of children with newly diagnosed clinical stage IV Burkitt lymphoma who achieved early complete metabolic remission after only two cycles of treatment with polatuzumab vedotin plus rituximab combined with chemotherapy. Notably, this represents the first reported application of polatuzumab vedotin in pediatric patients with newly diagnosed Burkitt lymphoma.